2015
DOI: 10.4172/2155-9570.1000395
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Leishmaniasis Presenting as Chronic Ulcerative Blepharoconjunctivitis: A Case Report

Abstract: Leishmaniasis is caused by unicellular eukaryotic obligate intracellular protozoa of the genus Leishmania that is endemic in over 98 countries in the world-most of which are developing countries including Ethiopia. It is transmitted by phlebotomine sandflies. The eye may be affected in cutaneous, mucocutaneous and Post Kala-Azar Dermal Leishmaniasis. We report a case of ocular leishmaniasis with eyelid and conjunctival involvement that had simulated ulcerative blepharoconjunctivitis not responding to conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Though well described, adnexal Leishmaniasis may be a diagnostic challenge, particularly in non-endemic areas or when it is not accompanied by any cutaneous lesions elsewhere on the body. [ 16 17 ] Authors have reported a long list of differentials, including chronic blepharitis,[ 18 ] pterygium,[ 17 ] hordeolum,[ 19 ] basal cell carcinoma,[ 20 ] squamous cell carcinoma,[ 16 ] impetigo,[ 21 ] histoplasmosis,[ 22 ] and an infected infundibular cyst. [ 23 ] Leishmaniasis can mimic many conditions and as such, a high index of suspicion is required.…”
Section: Resultsmentioning
confidence: 99%
“…Though well described, adnexal Leishmaniasis may be a diagnostic challenge, particularly in non-endemic areas or when it is not accompanied by any cutaneous lesions elsewhere on the body. [ 16 17 ] Authors have reported a long list of differentials, including chronic blepharitis,[ 18 ] pterygium,[ 17 ] hordeolum,[ 19 ] basal cell carcinoma,[ 20 ] squamous cell carcinoma,[ 16 ] impetigo,[ 21 ] histoplasmosis,[ 22 ] and an infected infundibular cyst. [ 23 ] Leishmaniasis can mimic many conditions and as such, a high index of suspicion is required.…”
Section: Resultsmentioning
confidence: 99%